INNOVATIVE PROJECT OF MECHANISM FOR TOOLS LAPAROSCOPIC - Mucha, Łukasz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
The article presents the analysis of available solutions of transmissions in laparoscopic tools. The proposed by an author a new transmission of laparoscopic tools has been described. Design and principle of operation as well as a simulations of possible movements of this tool has been also presented.